Comparative assessment of immunodiffusion and enzyme-linked immunosorbent assay used for bovine leukosis diagnosis - A. R. Mustafayev; M. O. Baratov (Ветеринария сегодня)
The implementation of animal health improvement and disease prevention activities with respect to bovine leukosis involves a need for timely detection of cattle infected with bovine leukaemia virus (BLV) on livestock farms. That is why early diagnosis using more sensitive and highly accurate methods is of particular importance. The paper presents the results of cattle serum tests for bovine leukosis with enzyme-linked immunosorbent assay (ELISA) and immunodiffusion (ID), as well as the comparative assessment of their effectiveness. A total of 440 cattle blood samples were subjected to serological testing with immunodiffusion; 37 (8.4%) of them tested positive for bovine leukaemia virus. The cattle blood samples were submitted from the Kumtorkalinsky (127), Karabudakhkentsky (122), Buynaksky (89) Raions, from Makhachkala (56) and Kaspiysk (46). Seropositivity was 17 (13.4%), 8 (6.6%), 5 (5.6%), 4 (7.1%) and 3 (6.5%), respectively. For the comparative assessment of the diagnostic tests, 100 (5 ID-positive and 95 ID-negative) serum samples were taken and tested with ELISA. As a result, specific antibodies against BLV gp51 antigen were detected in 4 ID-negative serum samples. All ID-positive serum samples also tested positive with ELISA. All in all 9 virus carriers were detected with ELISA, that is 44.4% more than with immunodiffusion. Thus, enzyme-linked immunosorbent assay is characterized by a higher sensitivity, as compared with immunodiffusion, and allows for improved detection of infected animals. However, alongside the advantages, this technique has certain disadvantages, one of which is the high price of the diagnostic test kit for anti-BLV antibody detection and the equipment required.